Tort Liability and Settlement Failure: Evidence on Litigated Auto Insurance Claims - Danial Asmat; Sharon Tennyson (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2016)
This paper empirically tests the predictions of the Priest-Klein model of pre-trial bargaining. It exploits variation in tort liability for bad faith insurance law across states and time during two decades of evolving law from the 1970s to the 1990s. Using repeated cross-sectional datasets of auto insurance claims from the Insurance Research Council, it nds evidence consistent with the hypothesis that variance in parties' subjective estimates of trial outcomes drove the likelihood of settlement. The likelihood of trial for an average claim is estimated to have risen by over 20% in the initial years following reform among the rst group of states to enact the tort remedy. Trial rates among tort states thereafter declined through the sample, dropping over 10% below control states by 1997. A similar relationship is estimated for the likelihood of a lawsuit being led, and characteristics of litigated claims are consistent with a di erent subset of claims being disputed following regime change. Results are robust to sample selection bias, endogeneity in settlement time, and other state-level legislation on punitive damages limits and prejudg- ment interest. While there is limited evidence for the predictions of asymmetric information models of settlement, we conclude that policyholders and insurers negotiated in a manner consistent with divergent expectations.
Keywords: 330